Energy-aware path strategy for embedded network - Yang-Hsin Fan (International Journal of Distributed Sensor Networks)
Silent and autonomous work drives embedded systems to closely connect human on daily life. Recently, more and more embedded systems join service chain to form greatly embedded networks. In addition, low-cost and speed time-to-market characteristics make the increase in embedded network being exponential. As a result, a new battleground of energy saving become a significant challenge as a huge amount of embedded systems collaborate with tasks. To combat energy consumption, we propose an energy-aware path strategy to achieve energy saving. It is designed for system level so as to early examine energy utilization. Our contribution focuses on modeling-embedded network by path matrix. Improving energy evaluation takes dynamic and static energy into consideration. Presenting a new approach on energy distribution evolves from XY coordination to circle domain. The advantages consist of fast modeling various paths and calculating energy consumption. The effectiveness of the proposed method is verified by a set of benchmarks, and the results achieve energy saving for intricacy path of embedded networks.